Analysis of Media Outlets on Women's Health: Thematic and Quantitative Analyses Using Twitter - Miguel A. Alvarez-Mon; Miguel A. Alvarez-Mon; Carolina Donat-Vargas; Carolina Donat-Vargas; Carolina Donat-Vargas; Maria Llavero-Valero; Maria Llavero-Valero; Alfredo Gea; Melchor Alvarez-Mon; Melchor Alvarez-Mon; Melchor Alvarez-Mon; Melchor Alvarez-Mon; et al. (Frontiers Media S.A., 2021)
Background: Media outlets influence social attitudes toward health habits. The analysis of tweets has become a tool for health researchers.Objective: The objective of this study was to investigate the distribution of tweets about women's health and the interest generated among Twitter users.Methods: We investigated tweets posted by 25 major U.S. media outlets about pre-menopausal and post-menopausal women's health between January 2009 and December 2019 as well as the retweets generated. In addition, we measured the sentiment analysis of these tweets as well as their potential dissemination.Results: A total of 376 tweets were analyzed. Pre-menopausal women's health accounted for most of the tweets (75.3%). Contraception was the main focus of the tweets, while a very limited number were related to infertility (1.4%). With regard to medical content, the effectiveness of contraceptive methods was the most frequent topic (46.2%). However, tweets related to side effects achieved the highest retweet-to-tweet ratio (70.3). The analysis of sentiments showed negative perceptions on tubal ligation.Conclusions: The U.S. media outlets analyzed are more interested in pre-menopausal than in post-menopausal women health and focused their content on contraception, while Twitter users showed greater interest in side effects.